The World of the Elseviers, 1580–1712 - Davies, David William. author. aut Link
159 p.
Keywords: IN the following pages an attempt has been made to give the essential facts of the history of the Elsevier family, and to show the relations of the printers to the world around them. Printing and publishing history is sometimes written as personal reminiscence, as aesthetic or technical criticism, or as a guide for book collectors. There is something to be said for treating it as a phase of economic or social history, and this treatment has been attempted here. There are difficulties inherent in the task which are not at first apparent. Printers are in touch on the one hand with the world of manufacturing and commerce, and on the other hand with the world of literature and scholarship - with not merely one phase of literature and learning but with a great many. As a result the innocent enthusiast who attempts to follow the activities of a publisher as he moves in the various milieux will constant ly find himself in strange regions he knows nothing about. He will probably wish he had never entered them, and his learned readers will probably wish so, too. So much assistance from friends has been sought and given that the story presented is a mosaic of the learning of others. The writer has reserved for himself only the special province of errors and omissions, and hereby lays claim to all such as may be found.